1991
DOI: 10.1111/j.1365-2044.1991.tb09560.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' desire for information about anaesthesia Scottish and Canadian attitudes

Abstract: Summary Patients in Canada and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
4
13

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 7 publications
2
64
4
13
Order By: Relevance
“…Another issue is patient desire for information, surrounding which there is an abundance of literature. [10][11][12] It has been shown that the majority of patients wish to meet with the anesthesiologist preoperatively and to be informed about a number of perioperative details, such as anesthetic complications and pain relief. 12 It has also been shown that there exists some public confusion as to the role of the anesthesiologist.…”
Section: Before Anesthesia After Anesthesia Consultation Consultationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another issue is patient desire for information, surrounding which there is an abundance of literature. [10][11][12] It has been shown that the majority of patients wish to meet with the anesthesiologist preoperatively and to be informed about a number of perioperative details, such as anesthetic complications and pain relief. 12 It has also been shown that there exists some public confusion as to the role of the anesthesiologist.…”
Section: Before Anesthesia After Anesthesia Consultation Consultationmentioning
confidence: 99%
“…[10][11][12] It has been shown that the majority of patients wish to meet with the anesthesiologist preoperatively and to be informed about a number of perioperative details, such as anesthetic complications and pain relief. 12 It has also been shown that there exists some public confusion as to the role of the anesthesiologist. 13 The "translation" of written material is important in the preparation of any patient educational material, as illiteracy, defined as a reading level below Grade 4, persists in every socio-economic and ethnic group.…”
Section: Before Anesthesia After Anesthesia Consultation Consultationmentioning
confidence: 99%
“…[1] Epidural anesthesia is popular and offers several benefits to the patients but at the same time it is linked with drawbacks like pain at the puncture site, fear of needles, and recall of the procedure. [13], [14], [15], [16]. These factors stress the importance of sedation that offers analgesia, anxiolysis, and amnesia.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding has been that the public appears disinterested in finding out more about anaesthetists [2]. Yet Lonsdale and Hutchison [3] found that patients rated meeting the anaesthetist as their single most important concern pre-surgery.…”
Section: Centre F O R Health Servicesmentioning
confidence: 99%